2006
DOI: 10.1002/ajmg.b.30300
|View full text |Cite
|
Sign up to set email alerts
|

A point mutation at the calreticulin gene core promoter conserved sequence in a case of schizophrenia

Abstract: Exposure to atypical antipsychotic drugs such as valproate increases the expression of chaperones that assist in the folding of proteins in the endoplasmic reticulum (ER) including calreticulin, GRP78/BiP, GRP94, and PD1. This neuroprotective role may be involved in the pathophysiology of neuropsychiatric disorders such as schizophrenia and bipolar disorder. The 5'-flanking region of the human calreticulin gene was screened in 100 cases of schizophrenia by PCR/SSCA between -485 and +1 basepair (bp) relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, the existence of a possible role played by ER stress and UPR modulators in the pathogenesis of clinically relevant conditions such as bipolar disorder and schizophrenia is further highlighted by two other genetic association studies, where mutations or SNPs have been identified in the genes encoding the ER-resident chaperones calreticulin and GRP94/GP96 (Aghajani et al, 2006; Kakiuchi et al, 2007). Also, PDI variants (Kwok et al, 2013), UBQLN2 and p62/ SQSTM1 mutations participate in ALS development (Deng et al, 2011; Teyssou et al, 2013).…”
Section: Impaired Upr Machinery As a Cause Of Neurodegenerationmentioning
confidence: 99%
“…Interestingly, the existence of a possible role played by ER stress and UPR modulators in the pathogenesis of clinically relevant conditions such as bipolar disorder and schizophrenia is further highlighted by two other genetic association studies, where mutations or SNPs have been identified in the genes encoding the ER-resident chaperones calreticulin and GRP94/GP96 (Aghajani et al, 2006; Kakiuchi et al, 2007). Also, PDI variants (Kwok et al, 2013), UBQLN2 and p62/ SQSTM1 mutations participate in ALS development (Deng et al, 2011; Teyssou et al, 2013).…”
Section: Impaired Upr Machinery As a Cause Of Neurodegenerationmentioning
confidence: 99%
“…With a lifetime prevalence of ∼0.32% [Perälä et al, 2007], schizoaffective disorder is considered as one of the most common psychiatric illnesses. We have recently reported a G > C point mutation located at position −48 within the core promoter of the calreticulin gene in a family case of paranoid schizophrenia also diagnosed with bipolar disorder [Aghajani et al, 2006]. The functionality of the mutation was studied in neural cortical cells, which revealed an aberrant expression of the gene in the mutant versus the wild‐type sequence [Nunes et al, 2008].…”
Section: Primer Sequences Used For the Screening Of The Human Calretimentioning
confidence: 99%
“…Our first report of mutation in the core promoter of the gene [Aghajani et al, 2006], in association with the whole‐genome linkage and functional data implicated the calreticulin gene as a promising candidate for the causation of the disease. Because none of the known genes located at the 19p13.2 interval have been linked to psychiatric disorders, calreticulin emerges as the best candidate gene whose dysregulation may trigger schizoaffective disorder.…”
Section: Primer Sequences Used For the Screening Of The Human Calretimentioning
confidence: 99%
“…Pharmacological evidence of the therapeutic effect of CALR (Bodmer and Bonilla 2008;Bown et al 2002;Chen et al 2000;Kim et al 2005;Shao et al 2006;Yuan et al 2001) in psychosis, further strengthen the role of CALR as a promising candidate in the causation of major psychiatric disorders. We have previously reported cases of psychosisassociated promoter mutations with estimated frequencies of less than 0.0007 in the general population (Aghajani et al 2006;Farokhashtiani et al 2011;Olad Nabi et al 2010). Those mutations occurred at positions -220 (rs138452745), -205 (rs556992558), and -48 (CR061331).…”
Section: Introductionmentioning
confidence: 97%